Study of Droplet Impact on Heated Surfaces Using Total Internal Reflection - Mohammad Khavari (2016)
The present study reports observations of the instantaneous boiling and spreading behaviors of ethanol droplets impacting on heated glass surface. By using the total internal reflection technique, we obtain the exact contact area between the liquid and the solid surface as the drop spreads out and boils as a function of time. We show that the contact area decreases with increasing temperature due to the formation and growth of vapor bubbles at the liquid-solid interface. The technique is useful for studying phenomena involving droplet-surface interaction, which is crucial in the emerging additive manufacturing technology.